PENERAPAN CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP KEPUASAN PELANGGAN CAMBRIDGE HOTEL MEDAN - Hisan, Khoirutun; Harianja, Rizky Andrian; Harahap, Yeni Maduma (Politeknik Pariwisata Medan, 2025)
Guest loyalty is a key factor in maintaining the sustainability of hotel businesses amid increasingly tight competition in the hospitality industry. This study aims to identify strategies to improve guest loyalty at Cambridge Hotel Medan through the implementation of Customer Relationship Management (CRM) activities and Porter’s value chain analysis. The research method uses a qualitative approach with data collection techniques through participatory observation and in-depth interviews with hotel management and several regular guests. The results show that Cambridge Hotel Medan can increase guest loyalty through service personalization, membership-based loyalty programs, two-way communication after visits, and CRM technology integration. In addition, the value chain analysis helps the hotel identify primary and supporting activities that add value to the guest experience. Recommendations include implementing an integrated CRM system, improving human resource quality, and optimizing digital communication with guests.